Comparative study between snodgrass urethroplasty and modified snodgrass urethroplasty for distal penile hypospadias in terms of post-operative urethrocutaneous fistula formation - Akan, Abu Bakar; Mondal, Susankar Kumar; Mojmdar, M. Rezaul Karim; Shakhawat Islam, M.; Mahammad, Noor; Munmun, Umme Habiba Dilshad (International Journal of Contemporary Pediatrics, 2022)
Background: Hypospadias is a congenital defect involving the male urethra characterized by the absence of urethral meatus at its normal position. This anomaly is usually associated with the ventrally deficient but dorsally hooded skin. In some cases, the penis is ventrally curved. Surgery is the option for this defect. So many procedures have been developed but none is free from the development of urethrocutaneous fistula. Now-a-days, the popular Snodgrass procedure is widely practiced but still fistula occurs. Many factors are thought to be responsible for it. The most important one is defective ventral penile skin which is deficient of vascular and collagen tissues. To minimize these deficient factors, a dorsal vascular preputial flap is transferred ventrally (modified) to reduce fistula formation further. A comparative study was disigned to determine the role of dorsal vascular flap. Methods: The prospective observational study was conducted in the department of pediatric surgery, Bangabandhu Sheikh Mujib medical university, Dhaka, Bangladesh since February 2017 to May 2021. Results: A total of 40 patients with distal penile hypospadias were included in this study. They were divided into Group A and group B, 20 for each. Snodgrass procedure was for Group A and the modified Snodgrass procedure was done for group B. The outcome of both the groups was determined in terms of fistula formation. Seven patients in group-A and one patient in group B developed fistula. The results were analyzed and were found statistically significant. Conclusions: Modified Snodgrass urethroplasty has a better outcome.